VD_FINDINFO HC / 2015 / 705 vom 24. August 2015 - VD Tribunal cantonal (2015)
PROTECTION DE L'UNION CONJUGALE, LOGEMENT, GARDE ALTERNÉE, OBLIGATION D'ENTRETIEN | 176 al. 1 ch. 1 CC, 176 al. 1 ch. 2 CC, 176 al. 3 CC